The Impact of Digital Implementation on the Daily Delivery Monitoring Process in Enhancing Business Process Efficiency and Customer Satisfaction - Nastiti, Sandra; Arviansyah, Arviansyah (Syntax Corporation, 2025)
In the midst of the rapid competition in the oil industry, strategies are needed to face global challenges and competition in the market. This study was conducted to show the impact of digital implementation on customer satisfaction levels. Digitalization will be focused on the supply and distribution services area, especially related to the speed and accuracy of delivery. This area was chosen since the customer satisfaction index scores in 2023 and 2024 got the same point. This indicates that there has been no significant development in the past year due to several issues faced by customers, such as being able to provide information to the team on site regarding the estimated arrival of the delivery unit, improving the delivery schedule, paying attention to the driver's speed, and communication and consistency in providing delivery updates. The study will use qualitative and quantitative methods. Qualitative approach is carried out through interview methods to identify user needs and translate it into key features in application proposed using House of Quality (HOQ) method. Meanwhile, quantitative approach is used to identify processes that need to be improved and evaluate lead time processes by comparing lead time processes before and after digital implementation through business process improvement, specifically through Material Information Flow Chart (MIFC). The output of this research is the creation of a digital application for monitoring daily deliveries that are integrated with Global Positioning System (GPS) installation. This is expected to improve accuracy regarding unit positioning and reduce dependence on human intervention.